Interaction with the Qur’an and self-regulated learning Vis-à-Vis academic achievement of undergraduate students - Ibrahim, Esam Eltigani Mohamed; Jani, Mohd. Shah; Alias, Alizi; Fatah Yasin, Raudlotul Firdaus; Zakariyah, Luqman (Excellent Publishers, 2015)

(untitled)
This study examined the interaction with the Qur’an and self-regulated learning (SRL) as predictors of academic achievement of undergraduate students in Malaysia. A total of 416Islamic Revealed Knowledge and Human Sciences undergraduate students from the International Islamic University Malaysia (IIUM) participated in this study. A questionnaire on interaction with the Qur’an is developed for the purpose of the present study. Selfregulated learning is measured using Kosnin’s (2007) questionnaire. Academic achievement was simply measured by the student’s cumulative grade point average (CGPA). Correlation and moderated regression tests were adopted to assess the relationship between the variables. The findings of this study revealed that there was moderate relationship between interaction with the Quran and academic achievement. Significant relationship between SRL and academic achievement was found. There is also moderate interaction effect of SRL and interaction with the Qur’an on academic achievement.